Management Strategies for Dry Eye Syndrome in Patients with Obesity—A Literature Review - Cosmin Victor Ganea; Călina Anda Sandu; Corina Georgiana Bogdănici; Camelia Margareta Bogdănici (Life, 2025)
Tear film alterations are commonly associated with ocular pathology. The tear film plays a vital role in maintaining the optical properties of the cornea and contains essential elements required for healing and preserving the integrity of the ocular surface. As a biological fluid, the tear film is easily collected using non-invasive techniques, making it a promising candidate for analysis and often referred to as an ideal biofluid. Several studies have attempted to identify biomarkers in the tear film that could be linked to systemic or ocular disorders, with the goal of developing tools for diagnosis or even early prevention. The quality and quantity of the tear film are influenced by hormonal status, emotional experiences related to social and familial events, and the work environment. Systemic disorders are often reflected at the ocular level through alterations in the tear film. Obesity is a well-recognized public health concern, extensively studied and investigated, much like other common systemic conditions. The presence of low-grade, chronic inflammation associated with excess body weight has been validated in several studies. The strategies for preventing obesity induced dry eye disease are based on regular physical activity, maintaining adequate hydration through sufficient fluid intake, weight loss, and the supplementation of essential fatty acids. This narrative literature review aims to highlight the tear film alterations associated with obesity. The article is intended for ophthalmologists, general practitioners, nutritionists, and researchers.